2018
DOI: 10.2139/ssrn.3203990
|View full text |Cite
|
Sign up to set email alerts
|

Achievement Gains from Attendance at Selective High Schools

Abstract: Academically selective high schools are a polarizing topic in education policy, despite only having a small presence in some Australian states. They appear successful. The schools regularly top annual school rankings of university entrance results, but this is perhaps unsurprising given that their students are admitted based on their performances on an entrance exam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 141 publications
0
0
0
Order By: Relevance
“…Australian selective schools are socioeconomically and ethnically more distinct from the student population than private schools (Ho, 2011;Tham, 2021), being socially more advantaged than high-fee private schools (Drew et al, 2020) and attracting substantially more private income than comprehensive public schools (Rowe & Perry, 2022). Research comparing similar students who attend selective and comprehensive secondary schools has found that selective schools offer limited-to-no additional value add in academic outcomes (Abdulkadiroğlu et al, 2014;Clark, 2007;Dobbie & Fryer, 2014;Zen, 2016) Such small additional academic gains are observed by selected students in primary school before selection (Coe et al, 2008) and is likely due to the high academic aspiration of students sitting entry tests (Houng & Ryan, 2018).…”
Section: Institutional Policies and Practicesmentioning
confidence: 99%
“…Australian selective schools are socioeconomically and ethnically more distinct from the student population than private schools (Ho, 2011;Tham, 2021), being socially more advantaged than high-fee private schools (Drew et al, 2020) and attracting substantially more private income than comprehensive public schools (Rowe & Perry, 2022). Research comparing similar students who attend selective and comprehensive secondary schools has found that selective schools offer limited-to-no additional value add in academic outcomes (Abdulkadiroğlu et al, 2014;Clark, 2007;Dobbie & Fryer, 2014;Zen, 2016) Such small additional academic gains are observed by selected students in primary school before selection (Coe et al, 2008) and is likely due to the high academic aspiration of students sitting entry tests (Houng & Ryan, 2018).…”
Section: Institutional Policies and Practicesmentioning
confidence: 99%